2015
DOI: 10.1002/cbf.3124
|View full text |Cite
|
Sign up to set email alerts
|

LINE‐1 hypomethylation induced by reactive oxygen species is mediated via depletion of S‐adenosylmethionine

Abstract: Whether long interspersed nuclear element-1 (LINE-1) hypomethylation induced by reactive oxygen species (ROS) was mediated through the depletion of S-adenosylmethionine (SAM) was investigated. Bladder cancer (UM-UC-3 and TCCSUP) and human kidney (HK-2) cell lines were exposed to 20 μM H2O2 for 72 h to induce oxidative stress. Level of LINE-1 methylation, SAM and homocysteine (Hcy) was measured in the H2O2 -exposed cells. Effects of α-tocopheryl acetate (TA), N-acetylcysteine (NAC), methionine, SAM and folic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 52 publications
(118 reference statements)
1
36
0
Order By: Relevance
“…SAM is utilized by DNMTs and histone methyltransferases and therefore, oxidative stress-mediated inhibition of SAM results in genomic hypomethylation (111). Similarly, LINE-1 methylation was shown to significantly decreased in H 2 O 2 treated HK-2 kidney cells (112). This study demonstrated that exposure of cells to ROS leads to homocysteine deficiency, which consequently causes SAM depletion and eventual hypomethylation of LINE-1 (112).…”
Section: Mechanism: Link Between Oxidative Stress and Epigenetic Genementioning
confidence: 57%
“…SAM is utilized by DNMTs and histone methyltransferases and therefore, oxidative stress-mediated inhibition of SAM results in genomic hypomethylation (111). Similarly, LINE-1 methylation was shown to significantly decreased in H 2 O 2 treated HK-2 kidney cells (112). This study demonstrated that exposure of cells to ROS leads to homocysteine deficiency, which consequently causes SAM depletion and eventual hypomethylation of LINE-1 (112).…”
Section: Mechanism: Link Between Oxidative Stress and Epigenetic Genementioning
confidence: 57%
“…Recently, Kloypan et al (2015) demonstrated that in colorectal cancer LINE-1 hypomethylation is associated with the oxidative stress-mediated activation of the ten-eleven translocation hydroxylase enzymes that cooperate with BER in controlling the formation and replacement of 5-hydroxymethylcytosine (5 hmC). Finally, ROS are considered to be responsible for aberrant DNA methylation in different cancer models (Campos et al , 2007; Lim et al , 2008; Quan et al , 2011; Ziech et al , 2011; Kloypan et al , 2015) and during chronic inflammation and inflammation-associated carcinogenesis, such as ulcerative colitis and Crohn's disease (Iborra et al , 2011; Hartnett and Egan, 2012). All these data suggest that increased oxidative DNA damage and/or lack of DNA repair are strongly correlated not only with genetic but also with aberrant DNA methylation in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in conditions of oxidative stress, methionine is required for the synthesis of cysteine to produce the antioxidant glutathione and is thus depleted for SAM synthesis (Cyr and Domann, ). In support, long‐term exposure to H 2 O 2 decreased SAM levels but increased glutathione levels, leading to hypomethylation of the long interspersed nuclear element‐1 (LINE‐1) (Kloypan et al , ). LINE‐1 hypomethylation as an indicator of global methylation status was found in blood from patients with ischaemic heart disease and stroke and has been related to higher risk for these diseases (Baccarelli et al , ).…”
Section: Effects Of Reactive Oxygen Species On Epigenetic Mechanismsmentioning
confidence: 99%